A bioinformatic approach of targeting SARS-CoV-2 replication by silencing a conserved alternative reserve of the orf8 gene using host miRNAs. (June 2022) - Goud, Vaggu Raghavendra; Chakraborty, Rajasree; Chakraborty, Averi; Lavudi, Kousalya; Patnaik, Sriram; Sharma, Swati; Patnaik, Srinivas
Abstract: The causative agent of the COVID-19 pandemic, the SARS-CoV-2 virus has yielded multiple relevant mutations, many of which have branched into major variants. The Omicron variant has a huge similarity with the original viral strain (first COVID-19 strain from Wuhan). Among different genes, the highly variable orf8 gene is responsible for crucial host interactions and has undergone multiple mutations and indels. The sequence of the orf8 gene of the Omicron variant is, however, identical with the gene sequence of the wild type. orf8 modulates the host immunity making it easier for the virus to conceal itself and remain undetected. Variants seem to be deleting this gene without affecting the viral replication. While analyzing, we came across the conserved orf7a gene in the viral genome which exhibits a partial sequence homology as well as functional similarity with the SARS-CoV-2 orf8 . Hence, we have proposed here in our hypothesis that, orf7a might be an alternative reserve of orf8 present in the virus which was compensating for the lost gene. A computational approach was adopted where we screened various miRNAs targeted against the orf8 gene. These miRNAs were then docked onto the orf8 mRNA sequences. The same set of miRNAs was then used to check for their binding affinity with the orf7a reference mRNA. Results showed that miRNAs targeting the orf8 had favorable shape complementarity and successfully docked with the orf7a gene as well. These findings provide a basis for developing new therapeutic approaches where both orf8 and orf7a can be targeted simultaneously. Graphical abstract: Image 1 Highlights: orf8 modulates the host immune system and suppresses it thereby helping the virus evade the immune surveillance. orf7a gene which is partially homologous to the orf8 gene sequence, performs a similar function by suppressing interferons and interacting with the host integrins via its Ig-like domain. Given the similarity between orf8 and orf7a, there is a possibility that miRNAs screened for orf8 region might have a binding affinity with orf7a region as well. Molecular docking studies explored the affinity of certain human miRNAs screened against orf8 towards orf7a region, suggesting that specific miRNA targeting both regions can potentially control the viral lifecycle.